2017
DOI: 10.1371/journal.pmed.1002277
|View full text |Cite|
|
Sign up to set email alerts
|

Risk prediction models for selection of lung cancer screening candidates: A retrospective validation study

Abstract: BackgroundSelection of candidates for lung cancer screening based on individual risk has been proposed as an alternative to criteria based on age and cumulative smoking exposure (pack-years). Nine previously established risk models were assessed for their ability to identify those most likely to develop or die from lung cancer. All models considered age and various aspects of smoking exposure (smoking status, smoking duration, cigarettes per day, pack-years smoked, time since smoking cessation) as risk predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
162
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 227 publications
(165 citation statements)
references
References 71 publications
3
162
0
Order By: Relevance
“…(WHO) World Mental Health Surveys(Auerbach et al, 2016). Prediction accuracy (AUC = 0.73) was comparable to the few prediction algorithms that have been evaluated for depression within a general population (AUC = 0.71)(Nigatu, Liu, & Wang, 2016) and primary care samples (AUC = 0.82)(Bellon et al, 2011) and are also comparable to other fields of medicine(Karnes et al, 2017;ten Haaf et al, 2017). Our data suggest that the first year in college constitutes a risk period for the onset of MDD.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…(WHO) World Mental Health Surveys(Auerbach et al, 2016). Prediction accuracy (AUC = 0.73) was comparable to the few prediction algorithms that have been evaluated for depression within a general population (AUC = 0.71)(Nigatu, Liu, & Wang, 2016) and primary care samples (AUC = 0.82)(Bellon et al, 2011) and are also comparable to other fields of medicine(Karnes et al, 2017;ten Haaf et al, 2017). Our data suggest that the first year in college constitutes a risk period for the onset of MDD.…”
supporting
confidence: 73%
“…Second, our study further adds to the cumulating evidence that the development of risk-prediction for psychiatric disorders is feasible (Bernardini et al, 2017) and provides evidence that a multivariate prediction model can be a useful tool to accurately predict the onset of MDD during college. Prediction accuracy (AUC = 0.73) was comparable to the few prediction algorithms that have been evaluated for depression within a general population (AUC = 0.71) (Nigatu, Liu, & Wang, 2016) and primary care samples (AUC = 0.82) (Bellon et al, 2011) and are also comparable to other fields of medicine (Karnes et al, 2017;ten Haaf et al, 2017). However, to achieve optimal performance, recalibration of models is needed prior to applying the models to a new population.…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 71%
“…However, while discrimination is an important statistical property, it does not properly address clinical usefulness [15,16,17,27,28,29]. For example, if a false negative decision causes greater harm than a false positive decision, a model with high sensitivity may be preferable to a model with high specificity and lower sensitivity, although the latter model might have, say, a higher AUROC.…”
Section: Model Evaluationmentioning
confidence: 99%
“…The LLP model also exhibited modest to good discrimination (AUCs, 0.67–0.82) when assessed alone in several European and U.S. study populations [44]. In more recent and extensive external validation studies, however, the PLCO M2012 model demonstrated the best performance, with respect to discrimination, calibration, sensitivity, and specificity, although not exceedingly better than the Bach model [45, 46]. In support, a study of >95,000 Australian smokers aged ≥45 years also found that the PLCO M2012 model displayed good calibration and discrimination (AUC, 0.80), and that its performance was largely driven by the main predictors of the Bach model, age and smoking history [47].…”
Section: Predicting Lung Cancer Risk Prior To Screening Initiationmentioning
confidence: 99%